5.3k views
3 votes
Simplyfy this expression

Simplyfy this expression-example-1
User DeltaTango
by
5.0k points

2 Answers

6 votes

Answer:

The correct answer is , the simplified form of expression 3m⁻²/5n⁻³ is

3n³/5m²

Explanation:

Identities

x⁻ᵃ = 1/xᵃ

1/x⁻ᵃ = xᵃ

The given expression is 3m⁻²/5n⁻³

To simplify the expression

By using the above identities we ca write,

3m⁻²/5n⁻³ = 3n³/5m² (since x⁻ᵃ = 1/xᵃ and 1/x⁻ᵃ = xᵃ)

The simplified form of expression 3m⁻²/5n⁻³ is 3n³/5m²

Therefore the correct answer is option D. 3n³/5m²

User Macpak
by
5.0k points
4 votes

Answer: OPTION D

Explanation:

To solve this problem you must keep on mind the following:

- The negative exponent rule says that:


a^(-n)=(1)/(a^(n))

- Power to power rule is:


(a^(m))^(n)=a^((m*n))

Therefore, keeping the information above on mind, you obtain:


(3m^(-2))/(5n^(-3))=(3n^(3))/(5m^(2))

User Stuti Rastogi
by
5.3k points